Herbal medicine (Gyejibongneyong-hwan) for treating primary dysmenorrhoea: a protocol for a systematic review of randomised controlled trials. Issue 9 (28th September 2016) - Lee, Ju Ah; Park, Sunju; Jung, Jeeyoun; Jun, Ji Hee; Choi, Jiae; Lee, Myeong Soo
Abstract : Introduction: Gyejibongneyong-hwan (GBH), also known as Guizhi Fuling formula, and is widely used for uterine fibroids in East Asian countries. Many clinical trials assessing the efficacy and safety of GBH formula for the treatment of dysmenorrhoea have been reported. This review will assess the clinical evidence for and against the use of GBH formula as a treatment for dysmenorrhoea. It will also discuss the proposed mechanism(s) that could link herbal medicine to improvements in dysmenorrhoea. Methods and analysis: Fourteen databases will be searched until September 2016. We will include randomised controlled trials (RCTs) examining GBH decoctions for any type of dysmenorrhoea. All RCTs of decoctions or modified decoctions will be included. The methodological qualities of the RCTs will be assessed using the Cochrane Collaboration tool for assessing risk of bias. Ethics and dissemination: This systematic review will be published in a peer-reviewed journal. The review will also be disseminated electronically and in print. It will be updated to inform and guide healthcare practices. Trial registration number: CRD42015023419.